What Is Bosniak, And What Bosnian-Herzegovinian Literature, And What Is, After All, The Bosnian-Hercegovinian Interliterary Community? (A Contribution To Literary-Theoretical And Literary-Historical Understanding) - Kodrić, Sanjin (Slavica Lodziensia, 2017)
Literary creation in Bosnia-Herzegovina is very complex. Viewed as a whole and throughout its historical duration, it has not been realized within the framework of one nation or one ethno-national community, nor within only one language or only one alphabet, nor within the framework of only one cultural-civilizational circle. This fact and this kind of literary-historical and cultural-historical reality gives the basis from which it is now possible to talk about a unique, singular literature of Bosnia-Herzegovina, or Bosnian-Herzegovinian literature, and also about parallel, plural literatures of Bosnia-Herzegovina – Bosniak as well as Croat and Serbian literatures in Bosnia-Herzegovina, together with the literary traditions of Bosnian-Herzegovinian minority communities, such as the Jewish community and others. Also, it is possible to speak about a phenomenon that should – given its own, internal historical-developmental dynamics and its literary-developmental principles and relationships in general – probably be named the Bosnian-Herzegovinian interliterary community. That is why, in understanding the phenomenon of literary creativity in Bosnia-Herzegovina, as well in defi ning Bosnian literary studies, primarily the theoretical concepts of interliterariness as well as closely related concepts of interculturality occur as potential solutions, as – both of them – have their essential meaning and full realization in the cases of both literary and culturally complex phenomena like literature in Bosnia-Herzegovina in general.